Investigating the potential of GDC electrolyte for High-Efficiency ITSOFC applications: short review - Roslan, Mohammad Fikrey; Abd Rahman, Hamimah; Abd Karim, Rafidah; Hussin, Mohamed Saiful Firdaus; Osman, Siti Hasanah (Academica Press Solutions, 2024)
Solid Oxide Fuel Cells (SOFCs) hold immense promise for clean and efficient power generation. However, conventional high-temperature SOFCs require operating temperatures exceeding 800°C, leading to material degradation and increased system complexity. Intermediate-Temperature SOFCs (ITSOFCs) offer a compelling solution, operating at lower temperatures (500-700°C) with benefits like faster startup, improved durability, and reduced system costs. A critical factor for achieving high efficiency in ITSOFCs is the electrolyte material. Gadolinium-doped Ceria (GDC) emerges as a promising candidate due to its high ionic conductivity at lower temperatures. This review explores the potential of GDC as an ITSOFC electrolyte, examining its advantages in conductivity, compatibility with operating temperatures, and its impact on overall cell efficiency. We discuss the challenges associated with GDC, such as limitations in achieving dense thin films and potential degradation issues. Additionally, the review highlights ongoing research efforts to address these challenges, including co-doping strategies and advanced thin film deposition techniques. By overcoming these obstacles, GDC-based electrolytes have the potential to revolutionize ITSOFC technology.